1992
DOI: 10.1083/jcb.117.6.1197
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of cholera toxin action on a polarized human intestinal epithelial cell line: role of vesicular traffic

Abstract: Abstract. The massive secretion of salt and water in cholera-induced diarrhea involves binding of cholera toxin (CT) to ganglioside GM1 in the apical membrane of intestinal epithelial cells, translocation of the enzymatically active A~-peptide across the membrane, and subsequent activation of adenylate cyclase located on the cytoplasmic surface of the basolateral membrane. Studies on nonpolarized cells show that CT is internalized by receptor-mediated endocytosis, and that the A~-subunit may remain membrane as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
153
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(163 citation statements)
references
References 65 publications
8
153
2
Order By: Relevance
“…If this is correct, it is also possible that the A 1 peptide of nicked CT or LT may not fully dissociate from the A 2 peptide and B subunit after entry into the cell. If so, this would fit nicely with our previous observations that in polarized cells signal transduction by CT is not diffusion-limited even after translocation of the A subunit (21) and that both the pentameric B subunit and translocated A subunit appear to travel together across the cell en route to the basolateral membrane (11). Alternatively, it remains possible that the A 1 peptide of both mutant and wt toxin may dissociate from the A 2 peptide/B subunit-G M1 complex after a small (but not measurable) amount of nicking by the same or another protease as discussed above or that proteolytic cleavage of the A subunit is not required for complete dissociation of A subunit from the B pentamer.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…If this is correct, it is also possible that the A 1 peptide of nicked CT or LT may not fully dissociate from the A 2 peptide and B subunit after entry into the cell. If so, this would fit nicely with our previous observations that in polarized cells signal transduction by CT is not diffusion-limited even after translocation of the A subunit (21) and that both the pentameric B subunit and translocated A subunit appear to travel together across the cell en route to the basolateral membrane (11). Alternatively, it remains possible that the A 1 peptide of both mutant and wt toxin may dissociate from the A 2 peptide/B subunit-G M1 complex after a small (but not measurable) amount of nicking by the same or another protease as discussed above or that proteolytic cleavage of the A subunit is not required for complete dissociation of A subunit from the B pentamer.…”
Section: Discussionsupporting
confidence: 66%
“…In contrast, when these same recombinant toxins were applied to apical membranes, there was little or no delay in the anticipated time course of the secretory response. In all past experiments (11,12,21,25,32), we consistently found that toxin preparations purified from V. cholerae supernatants elicited Cl Ϫ secretion with a shorter lag phase and more rapid rate of onset when applied to basolateral rather than apical surfaces of the same cells (Fig. 1, panel A).…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…To determine whether cholera toxin could directly stimulate intestinal epithelial cells to secrete PAF, we assayed PAF in supernatants and cells ofthe human intestinal T-84 cell line (obtained from the laboratory of K. Dharmsathaphor at the University ofCalifornia in San Diego). This cell line has been shown to respond to cholera toxin and other secretagogues with electrogenic chloride secretion (26,27). Cell monolayers cultured in a 1:1 mixe of Dulbecco's modified Eagle's mem and Ham's F12 (Gibco, Grand Island, NY) with 5% fetal bovine serum were exposed to cholera toxin (1 ;g/ml) for 2 hr.…”
Section: Introductionmentioning
confidence: 99%
“…The use of polarized human colonic epithelial T84 cells has greatly facilitated studies of Ctx and Etx, since toxicity can be readily monitored as the induction of electrogenic Cl Ϫ secretion (18). Toxin action is initiated by binding of the B-subunit moiety to cell surface receptors.…”
mentioning
confidence: 99%